Prevalence of considering revision rhinoplasty in Saudi patients and its associated factors - Najlaa Abdulrahman Alsubeeh; Mayar Abdulsalam AlSaqr; Mohammed Alkarzae; Badi Aldosari (SpringerOpen, 2019)
Abstract Background Primary rhinoplasty outcomes may not meet individual expectations. Consequently, reoperation may be advocated to improve results. This study examines the prevalence of individuals considering revision rhinoplasty, while identifying the main cosmetic and functional complaints and factors associated. Methodology This is a cross-sectional study conducted in Saudi Arabia using a self-reported online questionnaire distributed through social media channels. The sample included 1370 participants who were all Saudi nationals over the age of 16 who had undergone primary rhinoplasty at least 1 year prior. Results The prevalence of individuals considering revision rhinoplasty was 44.7%. The primary reason for considering it was the desire for further esthetic improvement in an already acceptable result (50.16%). The most common cosmetic complaints subjectively reported were poorly defined nasal tip (32.35%). The most prevalent nasal function symptom was nasal obstruction (56.9%). Significant factors associated with considering revision rhinoplasty included the physician not understanding the patient's complaints, short consultation time, low monthly income, inadequate information about the expected results, not using computer imaging to predict outcomes, lack of rapport with the surgeon, and inadequate information about the risks and complications. Conclusions A thorough understanding of patient concerns and expectations, as well as thoughtful consideration of risk factors, may help surgeons achieve more successful outcomes and potentially reduce the incidence of revision rhinoplasties. Level of evidence III